Left Ventricular Assist Device Performance Under Pressure: Troubleshooting Outflow Graft Dysfunction. (July 2020) - Belkin, Mark N.; Venturini, Joseph; Nathan, Sandeep; Grinstein, Jonathan
Abstract : Supplemental Digital Content is available in the text.